Peningkatan Literasi Sains Siswa Melalui Pendekatan Contextual Teaching And Learning (CTL) Bermuatan Etnosains (UPEJ Unnes Physics Education Journal, 2020)
The results of early observation at SMP N 3 Karanglewas show that the average scientific literacy of students is still relatively low, so an innovative learning approach is needed to train students' scientific literacy. This research aims to determine the effect of CTL implementation contained with ethnoscience on physics learning on student’s scientific literacy and determine its enhancement. This type of research is pre-experimental design with one group pretest-posttest design. Sampling technique in this research used purposive sampling at SMP N 3 Karanglewas. The sample in this study was class VIII C, amounting to 30 students. Aspects of scientific literacy in this research knowledge, context, competencies, and attitudes. The instruments used were student response questionnaires, observation sheets, learning devices, pretest and posttest. The results of the data obtained were analyzed using the normality test, t test, N-gain test, and calculation of the average aspects. The results showed that the average value of scientific literacy in the sample class was 77,57. The implementation of the CTL approach with ethnoscience on physics learning is able to increase student literacy skills by 0.583 which are in the medium category. So it can be concluded that the implementation of the approach to contextual teaching and learning (CTL) with ethnoscience on physics learning can increase students' scientific literacy skills.